Barriers to reporting nursing job errors from nurses’ viewpoint - marjaneh mardani; aziz shahraki (Journal of Holistic Nursing and Midwifery, 2009)
Introduction: Working errors are inevitable in every profession including health care professions, ‎but in nursing, it s of greater importance. ‎ Objective: The purpose of this study was to determine barriers to reporting nursing job errors from ‎nurses viewpoint.‎